Modeling the spread of dengue fever - Tay, Zhi Wei (2015)
Singapore had the worst dengue outbreak in year 2013 which had 8 death cases and 22,318 dengue cases. This had created the attention for the public to have greater awareness of dengue fever. National Environmental Agency (NEA) have implemented countermeasures to prevent the widespread of dengue with the use of technology. With the increased in the usage of technology, especially smartphones, mobile applications are getting more popular. Research and analysis have been carried out to see how the public can react more swiftly towards dengue fever with the use of technology. There are existing mobile applications that allows the public to report a dengue incident to play a part in monitoring dengue cases. However, such applications have their limitations. Therefore, Monitor Dengue is a mobile application that provides more details of dengue fever and other functions that the existing applications do not have such as better news coverage. Monitor Dengue consists of two major development which are android mobile development and C# dengue cases crawling development. The android mobile development will consists of pages for public user interaction and C# dengue cases crawling development will be for the administrator to input the latest dengue cases to be displayed on the mobile. Another minor development is the modification of the open source news crawling program to be customized for the usage of dengue news. The chosen architectural design for Monitor Dengue is Model-View-Controller (MVC) due to the most important benefit which is extensibility can be made easily. The system design is done through various Unified Modeling Language (UML) diagram to smoothen the development process. The development process requires the use of various software. The main software that were used are Eclipse for android development, Microsoft Visual Studio for web crawling of dengue cases, Notepad++ for PHP development and Python 2.7.6 (Shell) for dengue news crawling. After the development process is completed, Monitor Dengue was tested successfully using black box testing and white box testing. In the future, recommendation for monitor dengue could be extended for various diseases such as hand-foot mouth disease and extended coverage of dengue towards South-East Asia.